Exchange Rates and Economic Fundamentals : A Framework for Analysis - Symansky, Steven; Bartolini, Leonardo; Bayoumi, Tamim; Clark, Peter (Washington, D.C. : International Monetary Fund, 1994)
This paper summarizes the methods and types of indicators that are often employed, both insid and outside the IMF, to assess whether exchange rates are broadly in line with economic fundamentals.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet